Ginkgolic Acid as a carbapenem synergist against KPC-2 positive Klebsiella pneumoniae - Song, Yuping; Zou, Yinuo; Xu, Lei; Wang, Jianfeng; Deng, Xuming; Zhou, Yonglin; Li, Dan (Frontiers in Microbiology, 2024)
The successful evolution of KPC-2 in bacteria has limited the clinical practice of carbapenems. This dilemma deteriorated the prognosis of associated infections and hence attracted increasing attention from researchers to explore alternative therapeutic options. Here, the enzyme inhibition assay was first performed to screen for a potent KPC-2 inhibitor. The synergistic effect of the candidate with carbapenems was further confirmed by checkboard minimum inhibitory concentration (MIC) assay, time-killing assay, disk diffusion method, and live/dead bacteria staining analysis. The mechanisms by which the candidate acts were subsequently explored through molecular dynamics (MD) simulations, etc. Our study found that Ginkgolic Acid (C13:0) (GA) exhibited effective KPC-2 inhibitory activity in both laboratory strain and clinical strain containing KPC-2. It could potentiate the killing effect of carbapenems on KPC-2-positive Klebsiella pnenmoniae(K. pnenmoniae). Further explorations revealed that GA could competitively bind to the active pocket of KPC-2 with meropenem (MEM) via residues Trp104, Gly235, and Leu166. The secondary structure and functional groups of KPC-2 were subsequently altered, which may be the main mechanism by which GA exerted its KPC-2 inhibitory effect. In addition, GA was also found to synergize with MEM to disrupt membrane integrity and increase membrane permeability, which may be another mechanism by which GA reinforced the bactericidal ability of carbapenems. Our study indicated that GA was a significant KPC-2 inhibitor that could prolong the lifespan of carbapenems and improve the prognosis of patients.